Working for the Clampdown: State Repression and Confidence in Legal Authorities in Comparative Context - Davis, Andrew P. (The British journal of criminology, 2021)
Scholars have focussed on the national level factors affecting citizen perceptions of legal institutions, which vary a great deal across the world. Scepticism towards legal structures often arises as a result of corrupt or abusive practices on the part of legal actors that may poison relations between citizens and law enforcement. Empirical research on the cross-national determinant of confidence in the police have shown corruption to be an essential factor in predicting lower levels of confidence in the police. Yet, a focus on corruption oftentimes emphasizes the quality of governance and neglects abusive actions taken by officials that can undermine public trust. This article focusses on those abusive practices by examining the relationship between human rights and individual reports of confidence in legal authorities. Using a pooled sample across multiple waves of the World Values Survey and multilevel models, I test the extent to which protections from human rights abuses and perceptions of strong human rights practices are related to higher levels of confidence in legal authorities. Findings from the statistical analysis offer strong support for my theorized expectations.